The Influence of Work Performance, Social Security and Employee Incentives on Employee Job Satisfaction at PT. Bank Sumut Syariah Medan - Ridwan, Muhammad; Raja Syahputra Nasution (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study aims to determine the effect of work performance, social security and employee incentives both partially and simultaneously on employee job satisfaction at PT. Bank Sumut Syariah Medan. The data analysis techniques used are multiple regression analysis methods, Classical Assumption Test, t-test, F-test and Determination Test. Based on the results of the study, it can be concluded that the effect of work performance on employee job satisfaction is known that the Fcount value> Ftable (21.256> 2.82) which means that there is an effect of work performance, social security and employee incentives simultaneously on employee job satisfaction at PT. Bank Sumut Syariah Medan